2022
DOI: 10.3389/fmolb.2022.965403
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, evolution and function analysis of UGTs superfamily in cotton

Abstract: Glycosyltransferases mainly catalyse the glycosylation reaction in living organisms and widely exists in plants. UGTs have been identified from G. raimondii, G. arboreum and G. hirsutum. However, Genome-wide systematic analysis of UGTs superfamily have not been studied in G. barbadense. 752 UGTs were identified from four cotton species and grouped into 18 clades, of which R was newly discovered clades. Most UGTs were clustered at both ends of the chromosome and showed a heterogeneous distribution. UGT proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The number of TPSs from allotetraploid cotton was less than twice that of diploid cotton, which might be due to gene deletions during the evolutionary process of forming allotetraploid cotton. Gene loss is also present in the evolution of the GRX, AHL and UGT gene families ( Malik et al., 2020 ; Zhao et al., 2020 ; Sun et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of TPSs from allotetraploid cotton was less than twice that of diploid cotton, which might be due to gene deletions during the evolutionary process of forming allotetraploid cotton. Gene loss is also present in the evolution of the GRX, AHL and UGT gene families ( Malik et al., 2020 ; Zhao et al., 2020 ; Sun et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequences of four Gossypium species including G. hirsutum , ZJU; G. barbadense , HAU; G. arboreum , CRI; and G. raimondii, JGI were used to identify the gene family [21] . Protein sequences of tetraploid ( G. barbadense and G. hirsutum ) and diploid ( G. arboreum and G. raimondii ) cotton varieties were downloaded from Cotton FGD ( https://cottonfgd.org ) [22] . Additionally, genome datas of six other plants, A. thaliana, Vitis vinifera (V. vinifera), Populus trichocarpa (P. trichocarpa), Theobroma cacao (T. cacao), Oryza sativa (O. sativa) and Zea mays (Z. mays) were downloaded from the Phytozome V12.1 online site ( https://phytozome-next.jgi.doe.gov/ ) [23] .…”
Section: Methodsmentioning
confidence: 99%
“…The protein sequences were entered into the online MEME software to predicted the LCYs conserved motif sequence, The analysis was set to allow a maximum of 15 motifs, and other parameters were kept at default settings ( http://meme-suite.org/tools/meme ) [22] . Genome-wide annotation files and General Feature Format (GFF) files for four different cotton cultivars were acquired from CottonFGD ( http://www.cottonfgd.net/ ).…”
Section: Methodsmentioning
confidence: 99%
“…It was previously thought that group Q was specific to monocots, such as maize [54] and wheat [52]; however, the occurrence of Q members in Malus × domestica [41], Epimedium pubescens [35], and Triticum aestivum [52] suggested that group Q was not exclusive to monocots. Only one UGT in group R was found in Camellia sinensis [33] and other four species (Lotus japonicus, Medicago truncatula, Phaseolus vulgaris, and Trifolium pratense) [38], while there were 4, 4, and 6 UGT members belonging to the R group in P. granatum, Malus × domestica [41], and Gossypium raimondii [37], respectively, suggesting that group R may make an important contribution to the glycosylation of specific metabolites. Quantitatively, PgUGTs were concentrated in groups A, D, E, G, and L, indicating that members of these five groups expanded more rapidly than any other groups during plant evolution, as described by Caputi et al [7].…”
Section: The Classification Of Pgugts Based On Phylogenetic Treementioning
confidence: 96%